Contribution À Une Étude Floristique De « Aguelmouss–Moulay Bouaazza –Tiddass » (Plateau Central, Maroc) - Hachi, Mustapha; Rahou, Abdellah; Lamfadal, Kamal (European Scientific Journal, ESJ, 2016)
The study of wealth and floristic diversity, conducted during March, April, May and June 2015 in the region (Aguelmous - Moulay Bouazza - Oulmès- Tiddas- Maaziz) belonging to the central plateau, revealed the existence of 360 plant species; 46 species of Fabaceae, 44 Asteraceae, 32 and 19 respectively from Caryophyllaceae and Lamiaceae. These families comprise 43.9% of the entire flora of the study area, the rest of the species belong to 48 families with 56.10%. A significant number of endemic has been inventoried: 43 of Morocco, one of Morocco and the Iberian Peninsula 6 of Morocco and Algeria, 4 of Morocco, Algeria and Tunisia. Moreover, three rare and endangered species have been recorded. Also, ecological analysis based on floristic surveys between 230 m and 1630 m shows that the altitude is a discriminating factor in the distribution of vegetation.